2009
DOI: 10.1002/lapl.200810139
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic action of LED-activated pyropheophorbide-αmethyl ester in cisplatinresistant human ovarian carcinoma cells

Abstract: Cisplatin-resistance is a major obstacle for the successful therapy to ovarian cancer, and exploring novel approach to deactivate cisplatin-resistant ovarian cells will improve the clinical outcomes. Our present study showed that there was no dark cytotoxicity of MPPa in the COC1/DDP cells at the dose of 0.25 -4 μM, and LED-activated MPPa resulted in drug doseand light-dependent cytotoxicity. Apoptotic rate 6 h after LEDactivated MPPa (2 μM) increased to 16.71% under the light energy of 1 J/cm 2 . Confocal las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…After the experimental conditions, as reported above, the culture medium was removed and the viable cells that remained adhered to the glass substrate were fixed in 1 mL of buffered 2.5% glutaraldehyde for 24 hours and post-fixed with 1% osmium tetroxide for 1 hour. The cells adhered to the glass substrate were then dehydrated in a series of increasing ethanol concentrations (30,50,70,95, and 100%) and immersed in 1,1,1,3,3,3-hexamethyldisilazane (HMDS; Acros Organics, Springfield, NJ, USA) for 90 min, as described elsewhere (C.A. de Souza Costa et al, 2008) and stored in a desiccator for 24 h. The cover glasses were then mounted on metallic stubs, sputter-coated with gold and the morphology of the surface-adhered L929 and MDPC-23 cells was examined with a scanning electron microscope (JEOL-JMS-T33A Scanning Microscope, Tokyo, Japan).…”
Section: Analysis Of Cell Morphology By Scanning Electron Microscopy mentioning
confidence: 99%
“…After the experimental conditions, as reported above, the culture medium was removed and the viable cells that remained adhered to the glass substrate were fixed in 1 mL of buffered 2.5% glutaraldehyde for 24 hours and post-fixed with 1% osmium tetroxide for 1 hour. The cells adhered to the glass substrate were then dehydrated in a series of increasing ethanol concentrations (30,50,70,95, and 100%) and immersed in 1,1,1,3,3,3-hexamethyldisilazane (HMDS; Acros Organics, Springfield, NJ, USA) for 90 min, as described elsewhere (C.A. de Souza Costa et al, 2008) and stored in a desiccator for 24 h. The cover glasses were then mounted on metallic stubs, sputter-coated with gold and the morphology of the surface-adhered L929 and MDPC-23 cells was examined with a scanning electron microscope (JEOL-JMS-T33A Scanning Microscope, Tokyo, Japan).…”
Section: Analysis Of Cell Morphology By Scanning Electron Microscopy mentioning
confidence: 99%
“…The recently developed light emitting diode (LED) has many advantages, for examples, inexpensive, small volume, longer life and adjustable light intensity [3,12,13]. Emerging evidences have showed that LED is a suitable light source for the management of tumors [11].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the drawbacks of the current light sources, we have set up a new light source from light emitting diode (LED) in our laboratory. Our previous study showed that [3,10,11]. The objective of this study was to investigate that LEDactivated Pa induced the cellular destruction of colon cancer cells in vitro so as to provide a foundation for in vivo study and its clinical application in the management of colon cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPME seems, however, to be more effective at killing cisplatin-resistant ovarian cells, with which 16.71% of apoptosis has been reached. 41 …”
Section: Discussionmentioning
confidence: 99%